Clay-Alginate Beads Loaded with Ionic Liquids: Potential Adsorbents for the Efficient Extraction of Oil from Produced Water - Liaqat, Shehzad (2022)
Produced water (PW) generated from the petroleum industry, during the extraction of oil and gas, has harmful impacts on human health and aquatic life, due to its complex nature. Therefore, it is necessary to treat it before discharging it into the environment in order to avoid serious environmental concerns. In this research, oil adsorption from PW was investigated using clay-alginate beads loaded with ionic liquids (ILs), as the adsorbent material. The effects of several process parameters, such as the initial concentration of oil, contact time, pH, and temperature on the removal efficiency of the beads, were analyzed and optimized. Different characterization methods, such as the Fourier transform infrared spectrophotometer (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), and thermal gravimetric analysis (TGA), were used to investigate the surface morphology, the chemical bond structure and functional group, and the thermal stability of the ILs-based beads. The results revealed that the clay-alginate-ILs beads indicated a removal efficiency of 71.8% at the optimum conditions (600 ppm initial oil concentration, 70 min contact time, 10 pH, and at room temperature) with an adsorption capacity of 431 mg/g. The FTIR analysis confirmed the successful chemical bond interaction of the oil with the beads. The SEM analysis verified that the beads have a porous and rough surface, which is appropriate for the adsorption of oil onto the bead’s surface. The TGA analysis provides the thermal degradation profile for the clay-alginate-ILs. The beads used in the adsorption process were regenerated and used for up to four cycles.